Pengaruh Edukasi Berbasis Aplikasi Android “SEDIA” dalam Meningkatkan Self Efficacy Pasien Diabetes Mellitus Tipe 2 di Kota Kupang - Stefania Efenhilda Tefa; Welmince Paulina Nggorong (Universitas Malahayati, 2026)
ABSTRACT Diabetes mellitus (DM) is a chronic and progressive disease that causes quite serious complications in sufferers. One of the causes of the high number of complications is the lack of self-confidence in the ability of sufferers to carry out the 5 pillars of diabetes care independently optimally, which is related to the incidence of illness and also the quality of life of sufferers. One effort to increase self-efficacy is through providing education as a basis for forming perceptions that help sufferers adopt certain behaviors for their health. This study used a quantitative Quasi Experimental method with a Pretest and Posttest two Group Design research design, to analyze the effectiveness of the SEDIA application in increasing the self-efficacy of T2DM sufferers. Results: After respondents in the intervention group used the application for one month, there was an increase in self-efficacy among respondents in the control group. A total of 14 respondents (56%) felt confident in performing self-care at home, while 11 respondents (44%) felt doubtful. The Wilcoxon Sign Rank test showed a p value of 0.002 with an α value of 0.05. A p value α indicates that H0 is rejected, which indicates that the Android application-based educational program